Inborn Errors of Metabolism Associated With Autism Spectrum Disorders: Approaches to Intervention - Žigman, Tamara; Petković Ramadža, Danijela; Šimić, Goran; Barić, Ivo (Frontiers in Neuroscience, 2021)
Increasing evidence suggests that the autism spectrum disorder (ASD) is often associated with some of the inborn errors in metabolism, such as disorders of amino acid metabolism and transport (phenylketonuria, homocystinuria, S-adenosylhomocysteine hydrolase deficiency, branched-chain -keto acid dehydrogenase kinase deficiency, urea cycle disorders, Hartnup disease), organic acidurias (propionic aciduria, L-2 hydroxyglutaric aciduria), cholesterol biosynthesis defects (Smith-Lemli-Opitz syndrome), mitochondrial disorders (mitochondrial encephalomyopathy, lactic acidosis, and stroke-like episodes – MELAS syndrome), neurotransmitter disorders (succinic semialdehyde dehydrogenase deficiency), disorders of purine metabolism (adenylosuccinate lyase deficiency, Lesch-Nyhan syndrome), cerebral creatine deficiency syndromes, disorders of folate transport and metabolism (cerebral folate deficiency, methylenetetrahydrofolate reductase deficiency), lysosomal storage disorders (Sanfilippo syndrome, neuronal ceroid lipofuscinoses, Niemann-Pick disease type C), cerebrotendinous xanthomatosis, disorders of copper metabolism (Wilson disease), disorders of haem biosynthesis (acute intermittent porphyria) and brain iron accumulation disorders. In this review, we briefly describe aetiology, clinical presentation, and therapeutic principles, if they exist, for these conditions. Additionally, we suggest the primary and elective laboratory work-up for their successful early diagnosis.